2016
DOI: 10.1371/journal.pgen.1005811
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Analysis of Disease-Associated Point Mutations Unveils Profound Differences in mRNA Splicing of Peripherin-2 in Rod and Cone Photoreceptors

Abstract: Point mutations in peripherin-2 (PRPH2) are associated with severe retinal degenerative disorders affecting rod and/or cone photoreceptors. Various disease-causing mutations have been identified, but the exact contribution of a given mutation to the clinical phenotype remains unclear. Exonic point mutations are usually assumed to alter single amino acids, thereby influencing specific protein characteristics; however, they can also affect mRNA splicing. To examine the effects of distinct PRPH2 point mutations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 37 publications
1
17
0
Order By: Relevance
“…This approach utilizing minigenes harboring exons and the adjacent native introns (either full-length or abridged) has also been undertaken to assess defects of mRNA splicing caused by disease-associated variants in different genes, e . g ., PRPH2 [ 58 ], CLRN1 ( USH3A )[ 59 ], CNGβ1 [ 60 ]. A minimum of 200bp of intronic sequence from each end of the intron were used in generating abridged CFTR introns as this has been shown to be sufficient to capture the most critical splice regulatory sequences [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach utilizing minigenes harboring exons and the adjacent native introns (either full-length or abridged) has also been undertaken to assess defects of mRNA splicing caused by disease-associated variants in different genes, e . g ., PRPH2 [ 58 ], CLRN1 ( USH3A )[ 59 ], CNGβ1 [ 60 ]. A minimum of 200bp of intronic sequence from each end of the intron were used in generating abridged CFTR introns as this has been shown to be sufficient to capture the most critical splice regulatory sequences [ 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that the CFTR variant c.2988G>A, located in the last nucleotide of exon 18, results in partial missplicing [ 36 ] and a middle of exon ‘synonymous’ variant, c.2679G>T, has been reported to activate a cryptic splice site in CFTR exon 17 [ 68 ]. Importantly, these RNA-level effects of exonic variants have been reported in other disease-associated genes, such as ATP7B [ 69 ], DMD [ 15 ], and PRPH2 [ 58 ], thus our work emphasizes the need for careful evaluation of molecular consequences of exonic variants across the genome.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of PRPH2 mutations are sequence variants. Different mechanisms, including aberrant mRNA splicing, protein mislocalization, and protein degradation may cause a reduced expression of the protein in the rod outer segment [72]. …”
Section: Sequence and Copy Number Variationsmentioning
confidence: 99%
“…RdCVFL is normally expressed by cones as well as rods in the mouse retina, while the trophic factor RdCVF is specifically expressed by rods: alternative splicing of the Nxnl1 gene is restricted to rods [ 127 ]. Differences between splicing pattern between rods and cones were revealed by the study of the PRPH2 gene [ 128 ]. The cones and their outer segments composed of polyunsaturated fatty acids are damaged by reactive oxygen species produced from leakage of the respiratory chain.…”
Section: Oxidative Stress Promotes Retinal Diseasesmentioning
confidence: 99%